Access control security model based on behavior in cloud computing environment - Guo-yuan LIN; Shan HE; Hao HUANG; Ji-yi WU; Wei CHEN (Tongxin xuebao)
In view of the current popular cloud computing technology,some security problems were analyzed.Based on BLP(Bell-LaPadula) model and Biba model,using the access control technology based on behavior to dynamic adjusting scope of subject's visit,it put forward the CCACSM ( cloud omputing access control security model).The model not only guarantees the cloud computing environment information privacy and integrity,and makes cloud computing environment with considerable flexibility and practical.At last,it gives the model's part,safety justice and realization process.